2014
DOI: 10.1093/mnras/stu2193
|View full text |Cite
|
Sign up to set email alerts
|

On the dynamics of clouds in the broad-line region of AGNs with an ADAF atmosphere

Abstract: We investigate orbital motion of spherical, pressure-confined clouds in the broad-line region (BLR) of active galactic nuclei (AGN). The combined influence of gravity of the central object and the non-isotropic radiation of the central source are taking into account. While most of the previous studies assume that the pressure of the intercloud gaseous component is proportional to a power-law function of the radial coordinate, we generalize it to a case where the external pressure depends on both the radial dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…The Eddington ratio is denoted by l = La/L edd where La and L edd are the luminosity of the central source and the Eddington luminosity, respectively. In the absence of drag force, the above equations reduce to the main equations of the previous studies (e.g., Plewa et al 2013;Khajenabi 2015). We note that in our model each cloud is in pressure equilibrium with the ambient gas.…”
Section: General Formulationmentioning
confidence: 55%
See 1 more Smart Citation
“…The Eddington ratio is denoted by l = La/L edd where La and L edd are the luminosity of the central source and the Eddington luminosity, respectively. In the absence of drag force, the above equations reduce to the main equations of the previous studies (e.g., Plewa et al 2013;Khajenabi 2015). We note that in our model each cloud is in pressure equilibrium with the ambient gas.…”
Section: General Formulationmentioning
confidence: 55%
“…BLR clouds are subject to the anisotropic radiation pressure of a central source as has been pointed out by Liu & Zhang (2011). Recently, a few authors studied orbit of BLR clouds under combined effects of the central gravity and anisotropic radiation pressure (Krause et al 2011;Plewa et al 2013;Khajenabi 2015). For pressure-confined…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Khajenabi (2015) investigated orbital motion of spherical, pressure-confined clouds in the BLR of AGNs, and found that a disk-like configuration is more plausible for the distribution of the BLR clouds. For a pressure-confined cloud, rc(r) ∝ P −1/3 gas , where Pgas is the intercloud gas pressure and Pgas ∝ r −5/2 (Khajenabi 2015). Therefore, the cloud has a radius profile of rc(r) ∝ r 5/6 .…”
Section: Discussionmentioning
confidence: 99%
“…Radiation forces act on gas motions and make the f S dependent on Eddington ratio [e.g. (Netzer and Marziani, 2010;Khajenabi, 2015)]. The effect can be as large as a factor ≈ 2 and, perhaps more importantly, the efficiency of radiation forces is dependent on the gas column density, leading to the preferential expulsion of gas of lower column density (Netzer and Marziani, 2010).…”
Section: The Virial Factor: Orientation and Radiation Effectsmentioning
confidence: 99%